Genome-wide association study reveals novel genomic regions governing agronomic and grain quality traits and superior allelic combinations for Basmati rice improvement - Abhijith, Krishnan P.; Gopala Krishnan, S.; Ravikiran, Kuram Tirumala; Dhawan, Gaurav; Kumar, Pankaj; Vinod, Kunnummal Kurungara; Bhowmick, Prolay Kumar; Nagarajan, Mariappan; Seth, Rakesh; Sharma, Ritesh; Badhran, Sourav Kumar; Bollinedi, Haritha; et al. (Frontiers in Plant Science, 2022)
Genome-wide association studies (GWAS) are generally performed with diverse crop germplasm assemblies. However, association studies with elite breeding lines can be an efficient alternative as the results can be directly utilized in marker-assisted breeding. In the present study, GWAS was performed using 172 elite Basmati breeding lines, which were genotyped using an 80K SNP array. These lines were phenotyped for agronomic and grain quality attributes across seven environments including two consecutive Kharif seasons. Association analysis was performed using Bayesian-information and Linkage-disequilibrium Iteratively Nested Keyway (BLINK) model to identify the elite alleles and their combinations in the Basmati population. Three agronomic traits namely, days to fifty per cent flowering, plant height and panicle length, along with three, grain quality traits including kernel length before cooking, length breadth ratio and kernel length after cooking were considered for GWAS. We detected 32 unique MTAs including 11 robust MTAs for the agronomic traits and 25 unique MTAs including two robust MTAs for the grain quality traits. As many as six candidate genes associated with these MTAs were identified to be of particular relevance for respective traits, and 6 out of 13 robust MTAs were novel. The available allelic combinations of the robust MTAs for the corresponding traits in the population were investigated and superior allelic combinations were identified. This information was further utilized in selecting 77 elite genotypes from the panel. The present study generated valuable information that can be utilized in marker assisted selection to identify potential parental candidates for Basmati hybrid breeding program.